Evoluç\~ao geopolítica: Cenários e perspectivas - Sebasti\~ao C. Velasco e Cruz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The article analyses the major changes in the international system since the end of the Cold War. Taking as a starting point the question about the deep meaning of three events that have impacted the year of 2008 - global financial crisis; the deadlock in the negotiations of Doha round; the military conflict in South Georgia - it sketches the outline of the new power constellation that emerged in the 1990's; discusses three scenarios extracted from the debate on the probable evolution of the global power system (the scenarios multipolar; Consolidated unipolar, and liberal cosmopolit), and assesses the comparative plausibility of each, taking into account the developments that unfolded during the first decade of the 21 Century. Emphasizing the unilateral twist given by the Bush administration to the U.S. strategy, the article suggests that the three events referred to above should be understood as signs that the great strategy followed by the U.S. since the end of Cold War has been exhausted. A strategy founded on the idea of maintaining the superpower in its condition of uncontested world supremacy through an indefinite future.
Keywords: F59; 330